Creating projects for solving mathematical problems in Scratch - Grinev A. S. (Spring school marathon, 2018)
Programming is now a very relevant topic. This is due to the development and implementation in everyday life of information and communication technologies, the fact that no device in our time does not work without a written program. There are many programming languages that are designed to perform specific tasks. Scratch is much easier than all traditional programming languages. This work is devoted to the research of Scratch environment possibilities for solving mathematical problems. The projects of solving mathematical problems created by the author as a result of the research are published on the Scratch community website http://scrаtch.mit.edu
Keywords: программирование; язык программирования; programming; Scratch; Scratch; programming language